Penerapan metode analytical hierarchy process dan simple additive weighting dalam pengambilan keputusan siswa berprestasi pada sekolah menengah kejuruan. - Aulia Tegar Rahman; Sitti Muhartini; Astika Wulansari; Rizky Amirullah Hasiani; Arif Baktiar (JNANALOKA, 2021)
Vocational High School is a formal education unit that organizes vocational education that prepares students, especially to work in certain fields. In determining students who excel in certain fields, it is necessary to have a decision support system to improve the quality of decisions in determining students who excel from the highest average score. However, using the highest average score does not get optimal results because it is not adjusted to the existing needs in determining outstanding students. In this study, it can be used as a reference in making decisions for outstanding students by applying the Analytical Hierarchy Process and Simple Additive Weighting methods. The steps taken are: Data collection, Data Preprocessing, Ranking and Comparison of Results between Analytical Hierarchy Process, Simple Additive Weighting with manual weighting results. The results of the ranking comparison show that there are 6 students with the top ranking who are recommended to be outstanding students in the linguistic group.